Progressive Morality: An Essay in Ethics - Fowler, Thomas, 1832-1904 (Salt Lake City, UT : Project Gutenberg, 2004)
"Progressive Morality: An Essay in Ethics" by Thomas Fowler is an ethical treatise written in the late 19th century. The work explores moral principles, emphasizing the practical applications of ethics over theoretical debates. It aims to articulate a scientific understanding of morality that evolves alongside society's increasing intelligence and civilization. At the start of the essay, Fowler presents an overview of the relationship between morality, conduct, and the various sanctions that influence ethical behavior. He discusses the need to distinguish between different sanctions$1 (Bsuch as legal, social, and moral$1 (Band highlights how morality can be better understood through practical examples rather than abstract theories. Fowler posits that ethical investigation is often neglected due to discomfort with questioning established moral principles. He aims to provide a framework for understanding the development and education of moral sentiment, asserting that ethics must adapt over time as society progresses. (This is an automatically generated summary.)s
Release date is 2004-04-01
Produced by Shawn Cruze and PG Distributed Proofreaders. Produced from images provided by the Million Book Project
Keywords: Ethics, Evolutionary